Dead in the Water: The Vicious Cycle of Blanks During Natural Level 14 C Manipulation of Marine Algal Cultures - Kusch, Stephanie; Benthien, Albert; Richter, Klaus-Uwe; Rost, Björn; Mollenhauer, Gesine (Frontiers in Marine Science, 2019)
Authentic biomarker standards were obtained from algal cultures in an attempt to accurately determine blank C added during sample processing for compound-specific radiocarbon analysis. Emiliania huxleyi and Thalassiosira pseudonana were grown under manipulated Δ14C dissolved inorganic carbon (DIC) levels and chlorophyll a and either alkenones (E. huxleyi) or low molecular weight (LMW) alkanoic acids (T. pseudonana) were isolated from the respective biomass using preparative liquid chromatography (LC), wet chemical techniques or preparative gas chromatography, respectively. DI14C in the seawater medium was determined pre- and post-growth. Biomarker Δ14C values mostly agree within 1-2 analytical uncertainties. In those cases where biomarker Δ14C values differ significantly, chlorophyll a is up to 104‰ more 14C-depleted than alkenones or LMW alkanoic acids, consistent with a larger LC blank compared to the other purification methods. However, in the majority of experimental setups pre- and post-growth DIC Δ14C values seem to be compromised by an unknown and variable blank C contribution. DIC Δ14C values deviate strongly from the anticipated Δ14C values (by up to ca. 560‰), pre- and post-growth Δ14C values differ significantly (by up to ca. 460‰), and changes are not unidirectional. Accordingly, since the substrate Δ14C value cannot unequivocally be constrained, blank C contributions for the different biomarker purification methods cannot be accurately calculated. This study illustrates the challenges and problems of producing authentic standards that are not readily commercially available and exemplifies how a laborious and time-consuming culturing approach may enter a vicious cycle of blank C contamination hampering accurate blank C determination.